You and leukemia : a day at a time - Baker, Lynn S.; Roland, Charles G.; Gilchrist, Gerald S. (Philadelphia : Saunders, 2002)
Explains the causes, types, treatments, and complications of leukemi a and offers advice on learning to live with this disease.
Includes bibliographical references (p. 209-212) and index.
Keywords: Leukemia in children -- Juvenile literature; Leukemia